2015
DOI: 10.1111/mve.12139
|View full text |Cite
|
Sign up to set email alerts
|

A survey of tick‐borne pathogens in dogs and their ticks in the Pantanal biome, Brazil

Abstract: Tick and blood samples collected from domestic dogs in the Brazilian Pantanal were tested by molecular methods for the presence of tick-borne protozoa and bacteria. Among 320 sampled dogs, 3.13% were infected by Babesia vogeli (Piroplasmida: Babesiidae), 8.75% by Hepatozoon canis (Eucoccidiorida: Hepatozoidae), 7.19% by Anaplasma platys (Rickettsiales: Anaplasmataceae), and 0.94% by an unclassified Anaplasma sp. In three tick species collected from dogs, the following tick-borne agents were detected: (a) B. vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 26 publications
2
26
1
6
Order By: Relevance
“…Hepatozoon canis has been detected in several other tick species, including Amblyomma sculptum (Demoner et al, 2013;Melo et al, 2016), Dermacentor marginatus, (Hornok et al, 2013;Aktas, 2014;Karasartova et al, 2018), Dermacentor reticulatus (Hornok et al, 2013;Najm et al, 2014), Haemaphysalis concinna (Hornok et al, 2013;Andersson et al, 2017), Haemaphysalis parva (Orkun and Nalbantoğlu, 2018), Haemaphysalis punctata (Andersson et al, 2017), Haemaphysalis sulcata (Aktas, 2014), Ixodes canisuga, Ixodes hexagonus (Najm et al, 2014) and Ixodes ricinus (Gabrielli et al, 2010;Reye et al, 2010;Aktas, 2014;Najm et al, 2014;Hamsikova et al, 2016;Andersson et al, 2017). The vector competence of these species for H. canis is unknown, with many collected from H. canis-infected animals.…”
Section: A Better Understanding Of H Canis Vector Competence In Putamentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatozoon canis has been detected in several other tick species, including Amblyomma sculptum (Demoner et al, 2013;Melo et al, 2016), Dermacentor marginatus, (Hornok et al, 2013;Aktas, 2014;Karasartova et al, 2018), Dermacentor reticulatus (Hornok et al, 2013;Najm et al, 2014), Haemaphysalis concinna (Hornok et al, 2013;Andersson et al, 2017), Haemaphysalis parva (Orkun and Nalbantoğlu, 2018), Haemaphysalis punctata (Andersson et al, 2017), Haemaphysalis sulcata (Aktas, 2014), Ixodes canisuga, Ixodes hexagonus (Najm et al, 2014) and Ixodes ricinus (Gabrielli et al, 2010;Reye et al, 2010;Aktas, 2014;Najm et al, 2014;Hamsikova et al, 2016;Andersson et al, 2017). The vector competence of these species for H. canis is unknown, with many collected from H. canis-infected animals.…”
Section: A Better Understanding Of H Canis Vector Competence In Putamentioning
confidence: 99%
“…canis (Demoner et al, 2013;Melo et al, 2016). Although H. canis has been detected in questing I. ricinus (Reye et al, 2010;Hamsikova et al, 2016), which indicates that transstadial transmission occurs, there are no studies at present that have identified successful sporogony in I. ricinus (Gabrielli et al, 2010;Giannelli et al, 2013).…”
Section: A Better Understanding Of H Canis Vector Competence In Putamentioning
confidence: 99%
“…Both A. sculptum and A. tonelliae are aggressive to humans and domestic mammals and they have been incriminated as potential vectors of pathogenic microorganisms for domestic animals and humans (Guedes et al, 2005;Widmer et al, 2011;Soares et al, 2012;Alves et al, 2014;Labruna et al, 2014;Nunes et al 2015;Tarragona et al, 2015a;Melo et al, 2016;Tarragona et al 2016). Fatal cases of spotted fever in humans due to the infection with Rickettsia rickettsii were reported in localities of Jujuy and Salta Provinces, Argentina, and ticks of the A. cajennense species complex were recognized as the possible vectors (Ripoll et al, 1999;Paddock et al, 2008;Seijo et al, 2016).…”
mentioning
confidence: 99%
“…O aumento populacional de cães deve ser considerado dentro de programas de saúde pública, pois os ectoparasitas possuem ação espoliadora e são vetores de agentes de patogênicos para os cães e humanos (CASTRO; RAFAEL, 2006). Melo et al (2016) verificaram que 15,40% dos Amblyomma ovale amostrados estavam infectados por Rickettsia sp. e alertaram sobre como os seres humanos estão potencialmente expostos à infecção por agentes bacterianos e protozoários transmitidos por carrapatos.…”
Section: Introductionunclassified